Successful surgical management of an extrahepatic biliary cystadenocarcinoma - Márcio Lobo Guimarães (Rare Tumors, 2011)
Extrahepatic bile duct cancer is an uncommon disease, and few cases are curable by surgery. We report a case of extrahepatic biliary cystadenocarcinoma (BCAC) associated with atrophy of the left hepatic lobe. A 54-year old male was admitted with painless obstructive jaundice and a hepatic palpable mass noticed one month before presentation. Liver functions tests were consistent with cholestatic damage and serum carbohydrate antigen 19.9 (CA 19-9) was increased before treatment. Magnetic resonance imaging (MRI) disclosed dilatation of the left hepatic bile duct with irregular wall thickening close to the hepatic confluence, and atrophy of left hepatic lobe. The patient was submitted to en bloc extended left hepatectomy with resection of caudate lobe, hilar lymphadenectomy, and suprapancreatic biliary tree resection. All surgical margins were grossly negative, and postoperative course was uneventful, except for a minor bile leak. The patient was discharged on the 15th postoperative day; he is alive without tumor recurrence one year after primary therapy. Although technically challenging, extended en bloc resection is feasible in adults with extrahepatic BCAC and can improve survival with acceptable and manageable morbidity.